Combatants to Civilians Rehabilitation and Reintegration of Maoist Fighters in Nepal's Peace Process - Subedi, D.B (Rethinking Peace and Conflict Studies, 2018)
Much has been written about reintegration of ex-combatants in a traditional or conventional disarmament, demobilisation and reintegration (DDR) programme. This volume examines reintegration of ex-combatants in a un-conventional DDR in which a cash-based scheme replaced a reintegration programme. It uncovers the dilemmas surrounding the un-conventional DDR programme in Nepal, situating the phenomena in the divisive politics of war to peace transition. Drawing on the narratives and perceptions of ex-combatants and their families, the volume provides a compelling analysis of why some ex-combatants reintegrate socially and economically better than others at the end of a war. Analysing the consequences and effects of reintegration of Maoist ex-combatants in the post-conflict peace and security, the volume argues that cash-based schemed in DDR programme can pacify ex-combatants and de-politicise a DDR programme but cash alone can not reintegrate ex-combatants. DB Subedi lectures in Peace Studies in School of Humanities at the University of New England, Australia, and is a Senior Fellow at the Centre for Security Governance in Canada. He has previously work with many non-government organisations and United Nations agencies in South and South East Asia, especially Nepal, Sri Lanka, Myanmar, Viet Nam and the Philippines.